(untitled) (REVISTA NODO, 2017)
the human being transforms the natural landscape, and landscape shapes the identity of those who inhabit it. the result of this dynamic are cultural landscapes, in constant transformation, with varying degrees of anthropization. the dairy production landscape in the cold highlands of north Antioquia is an example of a cultural landscape. the intense productive vocation and strong visual elements in this landscape have been possible due to the rural population who transformed the Andean forest into a fragmented mosaic of pastures, food plantations, water bodies and non-productive spaces, according to the needs of each historical moment. Qis paper proposes a revision of this cultural landscape, based on fieldwork and permanent observation. It focuses on the significant values and social perceptions of the landscape and its natural structure. Furthermore, the article recognizes different constructions of identity within the landscape, scrutinizing subconscious representations beyond economic profit. the texts and images are result of the landscape experience of the author. they precedes the formulation of an investigation about cultural landscapes of dairy production in north Antioquia developed the Master of Landscape Design at UPB, Medellín, Colombia.